From SOMDA to application - integration strategies in the OR.NET demonstration sites - Rockstroh, Max; Dees, Raluca; Merzweiler, Angela; Schneider, Gerd; Bergh, Björn (Biomedical engineering, 2018)
The effective development and dissemination of the open integration for the next generation of operating rooms require a comprehensive testing environment. In this paper, we present the various challenges to be addressed in demonstration applications, and we discuss the implementation approach, the foci of the demonstration sites and the evaluation efforts. Overall, the demonstrator setups have proven the feasibility of the service-oriented medical device architecture (SOMDA) and real-time approaches with a large variety of example applications. The applications demonstrate the potentials of open device interoperability. The demonstrator implementations were technically evaluated as well as discussed with many clinicians from various disciplines. However, the evaluation is still an ongoing research at the demonstration sites. Technical evaluation focused on the properties of a network of medical devices, latencies in data transmission and stability. A careful evaluation of the SOMDA design decisions and implementations are essential to a safe and reliable interoperability of integrated medical devices and information technology (IT) system in the especially critical working environment. The clinical evaluation addressed the demands of future users and stakeholders, especially surgeons, anesthesiologists, scrub nurses and hospital operators. The opinions were carefully collected to gain further insights into the potential benefits of the technology and pitfalls in future work.
Gesehen am 14.04.2020